2014
DOI: 10.1007/s12028-014-9966-y
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability for Preclinical Detection of Secondary Complications After Subarachnoid Hemorrhage

Abstract: Introduction We sought to determine if monitoring heart rate variability (HRV) would enable preclinical detection of secondary complications after subarachnoid hemorrhage (SAH). Methods We studied 236 SAH patients admitted within the first 48 hours of bleed onset, discharged after SAH day 5, and had continuous electrocardiogram records available. The diagnosis and date of onset of infections and DCI events were prospectively adjudicated and documented by the clinical team. Continuous ECG was collected at 240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…19 Our results are in line with those of Papaioannou et al who found in 20 brain injured patients from multiple causes, including 3 patients with SAH, an association between decreased BRS and a high mortality rate (18). They are also in line with the results of Schmidt et al (30) who, assessed HR variability in the frequency domain in subarachnoid haemorrhage and identified an association between the LF/HF ratio (a ratio between the low frequency power and the high frequency power in RR intervals time series), which is an indicator of the sympathetic activity, and the occurrence of an infection or of a delayed ischemic deficit. In another study, Schmidt et al highlighted an association between a HR increase above 95 /minute lasting more than 12 hours and the 3-month functional outcome (31).…”
Section: Discussionsupporting
confidence: 93%
“…19 Our results are in line with those of Papaioannou et al who found in 20 brain injured patients from multiple causes, including 3 patients with SAH, an association between decreased BRS and a high mortality rate (18). They are also in line with the results of Schmidt et al (30) who, assessed HR variability in the frequency domain in subarachnoid haemorrhage and identified an association between the LF/HF ratio (a ratio between the low frequency power and the high frequency power in RR intervals time series), which is an indicator of the sympathetic activity, and the occurrence of an infection or of a delayed ischemic deficit. In another study, Schmidt et al highlighted an association between a HR increase above 95 /minute lasting more than 12 hours and the 3-month functional outcome (31).…”
Section: Discussionsupporting
confidence: 93%
“…HRV monitoring is a continuous, noninvasive tool increasingly used in the ICU in order to serve as a warning system and early detection application for worsening illness in critically ill patients [ 1 ]−[ 5 ] Recent applications of HRV monitoring include early diagnosis of sepsis in neonates [ 6 , 8 , 9 ] and adults [ 7 ], monitoring the depth of sedation in mechanically ventilated ICU patients [ 10 ] and preclinical detection of major adverse cardiopulmonary events [ 12 ] as well as secondary complications [ 11 ] after SAH. As these applications become crucial in the ICU setting, artifact-free HRV monitoring will be imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability (HRV) [ 1 5 ] monitoring is increasingly used in the intensive care unit (ICU) as a continuous noninvasive index with potential to serve as an early warning signal of worsening illness. Recent successful applications include detection of sepsis in neonates and adults [ 6 9 ], tracking the depth of sedation in patients on mechanical ventilation [ 10 ], and detection of delayed cerebral ischemia following subarachnoid hemorrhage (SAH) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have been using an array of offline analytical platforms such as Weka, R, SPSS, and big data platforms like Hadoop for the mining of large volumes of data. We have created applications of Weka analytics to build models able to predict secondary complication in neuro-ICUs [40]. Patient similarity concepts learned on historical data may allow physicians to make clinical decisions leveraging experiences gathered from data from similar patients observed in the past [41].…”
Section: B) Mining Patient Monitoring Data For the Discovery Of Earlymentioning
confidence: 99%